GAMBARAN DUKUNGAN KELUARGA TERHADAP MINUM OBAT PADA PASIEN STROKE DENGAN RIWAYAT HIPERTENSI DAN DIABETES DI POLI KLINIK PENYAKIT DALAM SANTOSA HOSPITAL BANDUNG - Purwo Suwignjo; Mery thania thania; Erna irawan Irawan; Lisna Anisa Fitriana Fitriana; Yuda Rizal Abdillah Abdillah (LPPM Universitas Adhirajasa Reswara Sanjaya, 2025)
Stroke is one of the most serious health problems with impacts that can cause disability and the third cause of death in the world both in developed and developing countries after heart disease and cancer. The cause of stroke can be caused by non-compliance in taking hypertension and diabetes mellitus medication. There are several factors that can affect the level of compliance in taking medication in This study aims to determine the relationship between family support and the level of compliance in taking medication in stroke patients at the internal medicine clinic of Santosa Hospital Bandung Central. The research design used a cross-sectional study with the Sperman-Rank correlation method. The population in this study was 93 patients. The inclusion criteria for this were patients who had stroke or recurrent stroke. The sampling technique used purposive sampling with a sample size of 59 patients. This study used an instrument that measured family support and the level of compliance in taking medication. Univariate analysis used the percentage technique and bivariate analysis used the Sperman-Rank correlation test. The results of the study showed that 45 (76.3%) or most had good family support.